SISTEM PAKAR DIAGNOSA PENYAKIT MALARIA PADA RSUD TANI DAN NELAYAN KABUPATEN BOALEMO - Muzakkir, Irvan (Teknosains: Media Informasi Sains dan Teknologi, 2016)
Malaria is an infectious disease caused by parasites of the genus Plasmodium, which is transmitted through the bite of Anopheles mosquito with an overview of the disease include fever are often periodic, anemia, enlargement of the spleen and various collection of symptoms due to effects on several organs such as brain, liver and kidneys. Because malaria is very dangerous, the authors designed a malaria disease diagnosis expert system that allows users to diagnose the onset of her illness. Expert systems are computer programs that mimic an expert reasoning with expertise in a particular knowledge area. Expert system trying to find a solution, give advice or conclusion that is consistent with thethe problems it finds. The author managed to implement a web-based expert system uses backward chaining method that can overcome these problems in consultation with the patient. Programming languages used in this system is the PHP programming language and for database creation using mysq. Hope the author, this system can help physicians or even ordinary people in making decisions when diagnosing malaria. Based on the results of white box testing concluded that this expert system error-free program for a total of Cyclomatic Complexity = 4, Region = 4, and Independent Path = 4.